"The world would just fall apart if there's no respect at all": children's understandings of respect for diversity in a post-conflict society. Issue 1 (2nd January 2017) - Burns, Stephanie; Lyons, Evanthia; Niens, Ulrike
Abstract: The term 'respect for diversity' has gained prominence in many policy and curricular developments aimed at promoting reconciliation and pluralism. To explore the understandings of 'respect for diversity' held by children in a society that has both emerged from conflict and is increasingly multicultural, 15 group interviews were conducted with 7–11-year-old children in Northern Ireland. The behavioural aspects of respect for diversity articulated by the children were identified as: attention; offering time; equality of treatment; and acts of solidarity. Affective motivations for these actions were empathy and the pursuit of friendship; cognitive motivations were: a moral norm of inclusion; curiosity; internalised human rights principles; and egalitarianism (a belief that all persons are equal in fundamental worth or value). Findings are discussed in relation to theories of children's prejudice development and moral development, and implications for the teaching and promotion of respect for diversity as part of peace education programmes are considered.